2019
DOI: 10.1002/anie.201911379
|View full text |Cite
|
Sign up to set email alerts
|

Dual Illumination Enhances Transformation of an Engineered Green‐to‐Red Photoconvertible Fluorescent Protein

Abstract: The molecular mechanisms for the photoconversion of fluorescent proteins remain elusive owing to the challenges of monitoring chromophore structural dynamics during the light-induced processes.W ei mplemented time-resolved electronic and stimulated Raman spectroscopies to reveal two hidden species of an engineered ancestral GFP-like protein LEA, involving semi-trapped protonated and trapped deprotonated chromophores en route to photoconversion in pH 7.9 buffer.Anew dual-illumination approach was examined, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(83 citation statements)
references
References 61 publications
2
81
0
Order By: Relevance
“…The I‐ring, however, has limited options and is rather challenging to modify because the two contributing amino acids are anchoring points to the β‐barrel enclosing the protein pocket. Nevertheless, most photoconvertible red FPs entail either a strong electron‐withdrawing group (e. g., asFP595, −COR) or a large conjugated group (e. g., Kaede‐like FPs, 4‐vinylimidazole), or both (e. g., far‐red PSmOrange) in the converted red form, which substantiates that the “one acceptor” at C‐2 position red‐shifts the FP emission by promoting a further delocalized and stabilized ICT state of the protein chromophore. Encouraged by these existing RFPs with an engineerable residue sidechain at the C‐2 site, we expect that the combination of double donor and one acceptor could further red‐shift FPs while retaining the photoconvertibility to benefit bioimaging applications.…”
Section: Discussionmentioning
confidence: 99%
“…The I‐ring, however, has limited options and is rather challenging to modify because the two contributing amino acids are anchoring points to the β‐barrel enclosing the protein pocket. Nevertheless, most photoconvertible red FPs entail either a strong electron‐withdrawing group (e. g., asFP595, −COR) or a large conjugated group (e. g., Kaede‐like FPs, 4‐vinylimidazole), or both (e. g., far‐red PSmOrange) in the converted red form, which substantiates that the “one acceptor” at C‐2 position red‐shifts the FP emission by promoting a further delocalized and stabilized ICT state of the protein chromophore. Encouraged by these existing RFPs with an engineerable residue sidechain at the C‐2 site, we expect that the combination of double donor and one acceptor could further red‐shift FPs while retaining the photoconvertibility to benefit bioimaging applications.…”
Section: Discussionmentioning
confidence: 99%
“…Blinking in the green state of mEos variants could affect photoconversion to the red state (39,40). The interplay between blinking and photoconversion has also been described in other photoconvertible fluorescent proteins, such as SAASoti (43) and LEA (44). Thus, combining our approach with singlemolecule measurements will offer a more complete and quantitative understanding of the photophysics of PAFPs or PCFPs.…”
Section: Intermediate State Of Meos32 That Converts To the Red Fluorescent State Upon 561-nm Illuminationmentioning
confidence: 65%
“…A protonated and twisted chromophore was also generated by irradiation of the green anionic cis chromophore in the FP LEA. 127 In this work, it was suggested that this state may be able to photoconvert upon 405 nm irradiation, but that photoswitching back to the anionic cis state is much more likely. For green mEos4b, a long-lived dark trans state was found upon 488 nm irradiation and characterized in detail.…”
Section: Photoactivation Mechanismsmentioning
confidence: 91%